Combination therapy incorporating Bcl‐2 inhibition with Venetoclax for the treatment of refractory primary plasma cell leukemia with t (11;14). (16th November 2017) - Gonsalves, Wilson I.; Buadi, Francis K.; Kumar, Shaji K.
Abstract: Primary plasma cell leukemia (pPCL) is the most aggressive form of the plasma cell (PC) malignancy, multiple myeloma (MM). It has been commonly associated with the presence of a chromosome translocation involving the immunoglobulin heavy chain (IgH) locus on 14q32, that is t (11;14). Results from early phase clinical trials utilizing the selective Bcl‐2 inhibitor, venetoclax, as a single agent in patients with relapsed MM have had remarkable efficacy among patients with t (11;14) abnormality. The present case demonstrates the ability of a combination regimen incorporating Bcl‐2 inhibition with daratumumab, bortezomib, venetoclax, and dexamethasone to induce a rapid and very deep hematologic response in a pPCL patient with t (11;14), even in a setting of very refractory disease. This case highlights the need to further study Bcl‐2 inhibition‐based therapy as an option for therapy in patients with pPCL with t (11;14).